Evaluation of Color Shifting in Structural Colored Resin Composite Using Two Instrumental Methods - Haidy Alnagdy; Rana Sedky; Khaled Nour (Ain Shams University, Faculty of Dentistry, 2024)
Aim: To observe the changes that occur in the color coordinates of Omnichroma when placed adjacent to different esthetic shades versus separately. Additionally assessing the ability of two instrumental methods in detecting these changes.Materials and Methods: A total of 18 adjoined blocks (measuring 10x6x4mm) and 6 separate resin composite blocks (measuring 10x12x4) were prepared using two metal molds. The adjoined blocks classified according to the two levels of study: Nano-hybrid resin composite (body shade A1, A2 and A3) and measuring device (Clinical spectrophotometry and Cross-polarized digital photography). The separate block is Omnichroma layered over 1mm Omnichroma blocker then adhered with different shades to fabricate the adjoined block.Both blocks are then measured using two instrumental methods clinical spectrophotometry VITA Easyshade V and cross-polarized digital photography. Then ΔL,Δa and Δb were calculated to show the color change between the Omnichroma separate versus adjoined.Statistical analysis was performed by One-way ANOVA, followed by Tukey's post hoc test. Comparison between both instrumental devices was analyzed using paired t-test.Results: One-way ANOVA showed a statistically significant difference in the color coordinates of Omnichroma separate versus adjoined using both instrumental devices.Paired t-test showed a statistically significant difference in measuring ΔL with all shades, Δa with A1 shade and no statistically significant difference in measuring Δb with both instrumental devices. Conclusion: Omnichroma universal composite exihibited a pronounced red-yellow structural color when approximated to different shades. This color change was better distinguished by cross-polarized digital photography.